Cinder Creative Coding Cookbook. - Dawid Gorny, Rui Madeira (Packt Publishing, 2013)
Full of easytofollow recipes and images that will teach powerful techniques and algorithms, building from basic projects to challenging applications. This book is for artists, designers, and programmers who have previous knowledge of C++, but not necessarily of Cinder.